Digital Crime In The Era Of Society 5.0: Juridical Analysis Of Cyber And Victim Protection - Handoko, Wahyu (Ipso Jure, 2025)
The development of digital technology in the era of Society 5.0 has presented new challenges in the form of increasing cybercrime that is complex, cross-border, and difficult to trace. On the other hand, Indonesia's legal system still focuses on punishing perpetrators, while protection for victims of digital crime has not received adequate attention. This study aims to analyze the effectiveness of applicable regulations juridically and highlight the need to change the legal paradigm from a retributive approach to a restorative one. This research uses normative legal methods with legislative, conceptual, and case approaches. The analysis was carried out on three main regulations: Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE), Law Number 27 of 2022 concerning Personal Data Protection (PDP), and Articles 373–379 in the Draft Criminal Code. Case studies of incidents of ransomware, phishing, and high-tech digital crime show weak victim protection, low public trust in the legal system, and the absence of a proper compensation scheme. The results of the study show that legal protection for victims is still scattered, not integrated, and lacks a restorative approach. Therefore, legal reform is needed through the drafting of a special law on cybercrime, improving the competence of law enforcement, establishing victim service centers, and strengthening international cooperation. Law enforcement in the era of Society 5.0 must transform, placing victim recovery as an essential part of fair, adaptive, and civilized criminal justice.